Identification of Mycobacterium tuberculosis DNA in a pre-Columbian Peruvian mummy. - Salo, W L (1994)
The existence of tuberculosis in the pre-Columbian Americas is controversial because the morphology of the lesion is not specific, the organism is culturally nonviable in ancient tissues, and nonpathogenic soil mycobacteria can contaminate buried bodies. We report the recovery of DNA unique to Mycobacterium tuberculosis from a lung lesion of a spontaneously mummified, 1000-year-old adult female body in southern Peru. This provides the most specific evidence possible for the pre-Columbian presence of human tuberculosis in the New World.